PKM PENGRAJIN LIMBAH PLASTIK di KLAMPOK KASRI, KEL. GADINGKASRI, MALANG - Arfida Boedirochminarni; Happy Febrina Hariyani (Studi Kasus Inovasi Ekonomi, 2020)
Creative MSME is a solution for the community group of Klampok Kasri Village, Gading Kasri Village, Klojen District, Malang City in improving their standard of living through plastic waste management. But the problem arises because of the limited knowledge in managing plastic waste and how to market the recycled products. The existence of this plastic waste craftsman needs special attention because it needs a lot of guidance, both in the field of capital, product manufacturing, product quality improvement, marketing, bookkeeping. The result of this dedication is that the craftsmen are able to be creative in processing recycled plastic waste and able to market it online through social media and e-commerce. In addition, the craftsmen are also able to make simple bookkeeping for the financial records of their businesses